2017
DOI: 10.1016/j.system.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Explaining listening comprehension among L2 learners of English: The contribution of general language proficiency, vocabulary knowledge and metacognitive awareness

Abstract: Listening comprehension constitutes a major problem for second language learners but little is known about the relative contribution of different factors to listening comprehension. Since there are still only very few studies in this area by comparison with studies focusing on the relationship between reading and vocabulary, there is a need for studies which can fill the gap in our knowledge about the specific contribution of generic and discrete-point measures of language ability to explaining listening. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
94
4
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(128 citation statements)
references
References 37 publications
(76 reference statements)
10
94
4
4
Order By: Relevance
“…Another issue raised in the literature review is construct confounding, which reduces the relevance of results from Oh (2016) and Wang and Treffers-Daller (2017) to the issue under consideration in this study. The relative importance of lexical and syntactic processes in L2 listening was not distinguished in Oh's (2016) results, while lexical knowledge was intertwined with general language proficiency in Wang and Treffers-Daller (2017). It is a pity that these studies do not provide further evidence for examining the theoretical relationship between lexical knowledge, syntactic knowledge, and L2 listening.…”
Section: Importance Of Theoretical Underpinningsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another issue raised in the literature review is construct confounding, which reduces the relevance of results from Oh (2016) and Wang and Treffers-Daller (2017) to the issue under consideration in this study. The relative importance of lexical and syntactic processes in L2 listening was not distinguished in Oh's (2016) results, while lexical knowledge was intertwined with general language proficiency in Wang and Treffers-Daller (2017). It is a pity that these studies do not provide further evidence for examining the theoretical relationship between lexical knowledge, syntactic knowledge, and L2 listening.…”
Section: Importance Of Theoretical Underpinningsmentioning
confidence: 99%
“…It is not uncommon for researchers to report different or even contradictory findings when they try to address the same issue in second language (L2) studies. A case in point is the relative importance of lexical and syntactic knowledge in L2 listening comprehension, where mixed findings have been reported, some alluding to the sole significance of lexical knowledge while downplaying or masking the role of syntactic knowledge (Mecartty, 2000;Staehr, 2009;Vandergrift and Baker, 2015;Cheng and Matthews, 2018;Matthews, 2018), others rendering the relative importance unclear (Oh, 2016;Wang and Treffers-Daller, 2017) or resorting to the more general construct of linguistic knowledge and avoiding the distinction between lexical and syntactic knowledge (Andringa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Skilled listeners and readers not only reply on language knowledge e.g., vocabulary, they also integrate contextual knowledge and general knowledge about the world into their understanding of speech or writing (Wang & Treffers-Daller, 2017). Learners focusing too much on decoding the incoming speech signal "deprive themselves of the opportunity to compensate for lack of linguistic knowledge through the use of cognitive and metacognitive strategies" (Stahr, 2009, p. 581).…”
Section: Strategy Use and Receptive Skillsmentioning
confidence: 99%
“…However, the significance was not consistent among the groups e.g., in the metacognitive strategies, advanced learners and lower intermediate learners differed significantly from one another, but not from upper intermediate learners. Wang and Treffers-Daller (2017) studied, among 151 non-English major university students in China, what proportion of the variance in listening comprehension was explained by general language proficiency, vocabulary size and metacognitive awareness. The results showed that vocabulary size was the strongest predictor followed by general language proficiency and metacognitive awareness was less important.…”
Section: Strategy Use and Receptive Skillsmentioning
confidence: 99%
“…The commonsense view of vocabulary assessment is to address this knowledge in the four separate skills, i.e., reading and listening (receptive skills) and writing and speaking (productive skills) (Fitzpatrick & Clenton, 2017). Many L2 vocabulary researchers have highlighted the potential relationship between vocabulary knowledge and the ability to read, write and listen in the target language (e.g., Alharthi, 2018Alharthi, , 2019Laufer & Aviad-Levitzky, 2017;Staehr, 2009;Wang & Treffers-Daller, 2017). With the exception of De Jong, Steinel, Florijn, Schoonen, and Hulstijn (2012), Koizumi and In'nami (2013), Milton, Wade, and Hopkins (2010) and Uchihara and Clenton (2018), it is almost certain that no study has attempted to examine the association between vocabulary knowledge and ability to speak in a Saudi setting.…”
Section: Introductionmentioning
confidence: 99%